Xanthine oxidase inhibition by allopurinol affects the reliability of urinary caffeine metabolic ratios as markers for N-acetyltransferase 2 and CYP1A2 activities - Fuchs, P.; Haefeli, Walter E.; Ledermann, H. R.; Wenk, Markus (European journal of clinical pharmacology, 1999)
Objectives: To evaluate the in vivo effect of xanthine oxidase (XO) inhibition by allopurinol on the determination of polymorphic N-acetyltransferase 2 (NAT2) and cytochrome P450 1A2 (CYP1A2) with urinary caffeine metabolic ratios.